To err is cumin - Budewitz, Leslie (Budewitz, Leslie. Spice shop mystery., 2024)
One person's treasure is another's trash . . .Pepper Reece, owner of the Spice Shop in Seattle's Pike Place Market, wants nothing more than to live a quiet life for a change. But when she finds an envelope stuffed with cash in a ratty old wingback left on the curb, she sets out to track down the owner. Pepper soon concludes that the chair and its stash may belong to young Talia Cook, new in town and nowhere to be seen. Boz Bosworth, an unemployed chef Pepper's tangled with in the past, shows up looking for the young woman, but Pepper refuses to help him search. When Boz is found floating in the Ship Canal, only a few blocks from Talia's apartment, free furniture no longer seems like such a bargain. On the hunt for Talia, Pepper discovers a web of connections threatening to ensnare her best customer. The more she probes, the harder it gets to tell who's part of an unsavory scheme of corruption--and who might be the next victim. Dogged by a sense of obligation to find the rightful owner of the hidden treasure, she keeps on showing up where she's not wanted, asking probing questions.One mistake, and she could find herself cashing out...--